Treatment of stable and unstable intertrochanteric fractures with selfdynamisable internal fixator (concept of double dynamisation) - Kostić, Igor Miodrag; Mitković, Milan M; Mitković, Milorad B (Vojnosanitetski pregled, 2015)
Bacground/Aim. Intertrochanteric fractures of the femur are the third most common fractures among all bone fractures. Today in everyday orthopedic practice a number of different methods of treatment of trochanteric fractures of the femur are applied. Despite the improvement in the development of new implants, the percentage of serious complications of the treatment of these fractures remains very high, varying from 10% to 20%. One of the most serious complications of internal fixation of intertrochanteric fractures is nonunion of fractures due to the lack of additional axial dynamisation of implants. The aim of this study was to determine the efficacy of double dynamisation in stable and unstable intertrochanteric fractures treatment using the self dynamisable internal fixator. Methods. During the period from 2000 to 2009 we analyzed the use of selfdynamisable internal fixator (SIF implant) in the treatment of 247 patients with stable and unstable intertrochanteric fractures. Fracture types were classified according to the AO Fracture Classification/Orthopaedic Trauma Association Scheme. Salvati and Wilson scoring systems were used for functional assessment considering pain, walking ability and hip movements of operated patients. Results. Of the total number of treated patients, 134 were males and 113 females, aged 19 to 90 (average 49.6) years. More than a half of the patients were older than 50 years. Monitoring of the patients after the operation was carried out clinically and radiographically for a period of three to six months in all the patients, whereas a 2-year follow-up was conducted in 176 (71.2%) patients. The average duration of surgery was 47 min, the average blood loss 145 mL, and the average fluoroscopy time was 16 sec (8–97 sec). The average time for union was 3.7 months (3–6.5 months). Double dynamisation (dynamisation along the neck and shaft of the femur) was observed in 85 (34.4%) patients, and was on average 4.3 mm (1.5–8 mm). All fractures managed with dynamisation implants healed completely within no later than six months after the surgery. In 17 cases there was a cut-out phenomenon of implant, while in seven cases there was mechanical implant failure. Complications were detected within 3 to 6 weeks after the surgery, and treated by the method of intramedullary fixation. During the study, there were no cases of infecton and thromboembolic complications detected. Conclusion. The concept of double dynamisation improves the fracture healing in the stable and unstable intertrochanteric fractures using the selfdynamisable internal fixator. This biological method of fixation provides healing of intertrochanteric fracture in the optimum period of time, significantly reducing the risk for mechanical failure.
Keywords: hip fractures; ortopedic procedures; internal fixators; fracture healing; treatment outcome